Human Campylobacteriosis in Italy: Emergence of Multi-Drug Resistance to Ciprofloxacin, Tetracycline, and Erythromycin - García-Fernández, Aurora; Dionisi, Anna M.; Arena, Sergio; Iglesias-Torrens, Yaidelys; Carattoli, Alessandra; Luzzi, Ida (Frontiers in Microbiology, 2018)
Campylobacter spp. is one of the main cause of bacterial gastroenteritis in the world. The increase of antibiotic resistance in this species is a threat to public health. A Campylobacter spp. surveillance study was performed in Italy in the 2013-2016 period by the Enter-Net Italia network. The most prevalent Campylobacter species identified causing gastroenteritis was C. jejuni (73.4%) and 45% of all the annual cases of campylobacteriosis were reported in the summer period. High rates of ciprofloxacin and tetracycline resistance in Campylobacter spp. have been observed. An increasing percentage of C. coli strains simultaneously resistant to ciprofloxacin, tetracycline and erythromycin has been found. Molecular mechanisms of resistance have been investigated and the role of efflux pumps evaluated. Antibiotic resistance in Campylobacter spp. is an increasing serious threat that requires coordinated action to minimize the emergence and spread of antimicrobial resistant strains from animals to humans throughout the food chain.